The Classification of Tapping techniques for Electric Bass - Khawhan, Bophit; Ketjaroen, Puttinun (Journal of Music and Performing Arts Khon Kaen University, 2025)
The technique of tapping on an electric bass involves using both hands together to press both fingers on the fretboard. There are two types of tapping techniques that can be classified. For instance, 1) Touch style tapping involves using both hands' fingers to press on the fretboard. The tone can be short or long depending on how long the strings are pressed on the fretboard. 2) Linear tapping involves placing the fingers of the right and left hands on the string in a hammer on and pull off manner. A variety of tapping techniques can be created and developed by the player such as arpeggio tapping, scale fragments tapping, tapped bends, chords stack tapping style, accompaniment tapping style, double stop tapping style, polyphony tapping style, artificial harmonic tapping style. Furthermore, it can be combined with other techniques such as slapping with tapping, and tapping with strumming.